Smart Halal Business: Inovasi Digital Dalam Sertifikasi, Branding, Dan Kepercayaan Konsumen - Mustajab, Sahal (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2025)
Digital transformation has significantly impacted the development of the halal industry, particularly in the areas of certification, branding, and consumer trust. The concept of smart halal business emerged in response to market demands for transparency, efficiency, and innovation in managing the halal value chain. This study aims to analyze the role of digital innovation in supporting the sustainability of halal businesses through the integration of technology into certification systems, branding strategies, and building consumer loyalty. The research method used a qualitative approach with literature studies and descriptive analysis of best practices in Indonesia and globally. The results show that digitalization of halal certification, such as the use of mobile applications, blockchain, and big data analytics, can increase accountability and facilitate access for business actors. On the branding side, the use of digital marketing and e-commerce platforms expands market reach and strengthens the image of halal products. Meanwhile, digital innovation contributes to increased consumer trust through information transparency and more personalized interactions. This study confirms that the implementation of smart halal business not only supports the competitiveness of halal MSMEs but also strengthens Indonesia's position in the global halal industry ecosystem.